2010
DOI: 10.1002/gepi.20492
|View full text |Cite
|
Sign up to set email alerts
|

The gene, environment association studies consortium (GENEVA): maximizing the knowledge obtained from GWAS by collaboration across studies of multiple conditions

Abstract: Genome-wide association studies (GWAS) have emerged as powerful means for identifying genetic loci related to complex diseases. However, the role of environment and its potential to interact with key loci has not been adequately addressed in most GWAS. Networks of collaborative studies involving different study populations and multiple phenotypes provide a powerful approach for addressing the challenges in analysis and interpretation shared across studies. The Gene, Environment Association Studies (GENEVA) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 24 publications
(24 reference statements)
0
125
0
Order By: Relevance
“…4,5,9,10 The UGT1A cluster encodes 9 transferase genes (UGT1A* 1, 3,4,5,6,7,8,9,10), of which 8 are known active gene transcripts. All of the UGT1A proteins are identical in the amino acid sequence encoded by exons 2 through 5 with unique alternate first exons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,9,10 The UGT1A cluster encodes 9 transferase genes (UGT1A* 1, 3,4,5,6,7,8,9,10), of which 8 are known active gene transcripts. All of the UGT1A proteins are identical in the amino acid sequence encoded by exons 2 through 5 with unique alternate first exons.…”
Section: Discussionmentioning
confidence: 99%
“…2 The GENEVA (Gene Environment Association Studies) Study of Venous Thromboembolism of the National Human Genome Research Institute enrolled consecutive Mayo Clinic outpatients with objectively diagnosed deep venous thrombosis and/or pulmonary embolism who resided in the upper Midwest and had been referred by a Mayo Clinic physician to the Mayo Clinic Special Coagulation Laboratory or to the Mayo Clinic Thrombophilia Center. 6 A deep venous thrombosis or pulmonary embolism was categorized as objectively diagnosed (1) when it was confirmed by venography or pulmonary angiography or via a pathology examination of a thrombus removed at surgery or (2) if findings on at least 1 noninvasive test (compression duplex ultrasonography, lung scan, computed tomography, magnetic resonance imaging) were positive. Persons with venous thromboembolism related to active cancer were excluded.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Large-scale international efforts are underway to dissect the genetics of these common conditions (Cornelis et al 2010;Sullivan 2010;Ehret et al 2011;Rivas et al 2011;Yang et al 2012). However, of the thousands of significant associations between genetic variants and complex traits or disease, most account for only a modest portion of overall trait variability (Visscher et al 2012;Robinson et al 2014).…”
Section: Insights From Mouse Modelsmentioning
confidence: 99%
“…Thus, depending on the goals of a study, measures of alcohol consumption can be collected by using food-frequency questionnaires, from medical charts, via self-report in case-control studies of health-related outcomes, and from interviews in studies for addiction and other psychiatric disorders. To illustrate this remarkable variation in the assessment of alcohol consumption, representative alcohol-consumption measures from individual studies of the GENEVA Consortium are shown in Table 1 (46,47).…”
Section: Why Measurement Heterogeneity Occursmentioning
confidence: 99%